Comparative Genomics of the Eukaryotes - Rubin, Gerald M.; Yandell, Mark D.; Wortman, Jennifer R.; George L. Gabor Miklos; Nelson, Catherine R.; Hariharan, Iswar K.; Fortini, Mark E.; Li, Peter W.; Apweiler, Rolf; Fleischmann, Wolfgang; Cherry, J. Michael; Henikoff, Steven; et al. (Science (American Association for the Advancement of Science), 2000)
A comparative analysis of the genomes of Drosophila melanogaster, Caenorhabditis elegans, and Saccharomyces cerevisiae-and the proteins they are predicted to encode-was undertaken in the context of cellular, developmental, and evolutionary processes. The nonredundant protein sets of flies and worms are similar in size and are only twice that of yeast, but different gene families are expanded in each genome, and the multidomain proteins and signaling pathways of the fly and worm are far more complex than those of yeast. The fly has orthologs to 177 of the 289 human disease genes examined and provides the foundation for rapid analysis of some of the basic processes involved in human disease.